2015
DOI: 10.1086/682051
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic and synergistic responses to solar ultraviolet radiation and increased temperature of phytoplankton from cenotes (sink holes) of the Yucatán Peninsula, México

Abstract: Cenotes (sink holes) are karstic formations characteristic of the Yucatán Peninsula and are the main source of fresh water in the region. Because of their tropical location, they receive high levels of solar radiation and are exposed to high temperatures. However, the effect of these global-change-related variables on phytoplankton in cenotes is unknown. We carried out experiments with phytoplankton communities collected from 2 cenotes differing in their penetration of solar radiation (Leona Vicario [LV]: turb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Though the biodiversity in the SYP is known, with the presence of phytoplankton, rotifers, cladocerans, copepods, macroscopic invertebrates (Iliffe, 1993), more than 45 species of crustaceans (Alvarez et al , 2015) and almost 40 species of fish (Schmitter‐Soto and Gamboa‐Pérez, 1996), in the present decade new taxa continue to be registered. However, research carried out on microorganisms living in these environments is scarce, without taking into account the reports due to anthropogenic contamination, they are found in plankton and phytoplankton (Sánchez et al , 2002; Aké‐Castillo, 2014; Irola‐Sansores et al , 2014; Szeroczyńska and Zawisza, 2015; Villafañe et al , 2015); fungal biomass (Gómez‐Reyes et al , 2017); tropical microscopic fungi (Gamboa‐Angulo et al , 2012; Moreno‐Pérez et al , 2014; Moreno‐Pérez et al , 2016); sediments from anchialine caves (Van Hengstum et al , 2009); and moderately halotolerant bacteria (De La Rosa‐García et al , 2007). In comparison with the bacterioplankton estimations of 5.8 × 10 2 –8.0 × 10 3 cells/mL in some sinkholes and their associated caves (Alcocer et al , 1999), the proportion of microorganisms identified is scarce; however, they have given notoriously relevant evidence of their biotechnological potential as mentioned below.…”
Section: Discussionmentioning
confidence: 99%
“…Though the biodiversity in the SYP is known, with the presence of phytoplankton, rotifers, cladocerans, copepods, macroscopic invertebrates (Iliffe, 1993), more than 45 species of crustaceans (Alvarez et al , 2015) and almost 40 species of fish (Schmitter‐Soto and Gamboa‐Pérez, 1996), in the present decade new taxa continue to be registered. However, research carried out on microorganisms living in these environments is scarce, without taking into account the reports due to anthropogenic contamination, they are found in plankton and phytoplankton (Sánchez et al , 2002; Aké‐Castillo, 2014; Irola‐Sansores et al , 2014; Szeroczyńska and Zawisza, 2015; Villafañe et al , 2015); fungal biomass (Gómez‐Reyes et al , 2017); tropical microscopic fungi (Gamboa‐Angulo et al , 2012; Moreno‐Pérez et al , 2014; Moreno‐Pérez et al , 2016); sediments from anchialine caves (Van Hengstum et al , 2009); and moderately halotolerant bacteria (De La Rosa‐García et al , 2007). In comparison with the bacterioplankton estimations of 5.8 × 10 2 –8.0 × 10 3 cells/mL in some sinkholes and their associated caves (Alcocer et al , 1999), the proportion of microorganisms identified is scarce; however, they have given notoriously relevant evidence of their biotechnological potential as mentioned below.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the global change impact have mainly focused on the responses of individual variables on aquatic communities (e.g., eutrophication: Smith et al, 1999, ultraviolet radiation: Williamson et al, 1999; more recently, however, several studies have highlighted the importance of considering multivariables approaches to better understand and predict how communities will respond to complex future environmental conditions (Garcia et al, 2013;Boyd et al, 2016). This is because in Nature, ecosystems are simultaneously subjected to the action of multiple variables which may act in a synergistic or antagonistic manner (Crain et al, 2008;Dunne, 2010); thus the observed responses do not necessarily represent the sum of the individual effects of each variable (Villafan ˜e et al, 2015a). For example, previous studies showed that high nutrient availability reduces the negative effects of UVR by improving the phytoplankton's photosynthetic performance (Heraud et al, 2005;Marcoval et al, 2007;Cabrerizo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This can promote greater heterotrophy by increased community respiration (Martínez‐García et al ), thus altering the energy transfer to higher trophic levels (Tsagaraki et al ). On the other hand, it is known that current or enhanced levels of UVR inhibits the PP (Helbling et al ; Villafañe et al ), nutrient uptake (Hessen et al ), Φ PSII or DNA repair (Jeffrey et al ; Harrison et al ; Villafañe et al ); however, although the combined impact of both global change drivers is generally considered antagonistic (e.g., nutrients attenuate the harmful effect of UVR), recent results by Carrillo et al () and Harrison et al () evidence that nutrient inputs can also unmask the harmful UVR effects on planktonic responses.…”
mentioning
confidence: 99%